Completion surgery following transanal endoscopic microsurgery: assessment of quality and short‐ and long‐term outcome. (24th October 2013) - Hompes, R.; McDonald, R.; Buskens, C.; Lindsey, I.; Armitage, N.; Hill, J.; Scott, A.; Mortensen, N. J.; Cunningham, C.
Abstract: Aim: Patients with unfavourable pathology after transanal endoscopic microsurgery (TEM) should be offered completion surgery (CS) if appropriate. The aim of this retrospective cohort study was to assess the short‐term outcome and long‐term oncological results of CS and identify factors compromising the quality of resection specimens. Method: Data were retrieved and analysed on patients who underwent CS from a comprehensive national TEM database (1992–2008) and the institutional prospective database from the Oxford University Hospitals (2008–2011). Results: There were 36 patients eligible for analysis. Postoperative complications occurred in 19 and were minor (grade I–II) in 13 and major (grade III–V) in six patients. The quality of the resected specimen was graded as good in 23 (64%), moderate in six (16.6%) and poor in seven (19.4%). Full‐thickness excision by TEM ( P  =   0.03), an interval to CS greater than 7 weeks ( P  =   0.05) and distally located lesions ( P  =   0.04) were associated with increased risk for an inferior surgical specimen. Overall survival after CS was 91% at 1 year and 83% at 5 years. Patients with a 'good' TME specimen had significantly improved disease‐free survival compared with patients with an 'inferior' specimen (100 vs 51%, P  =   0.001). Conclusion: Patients having full‐thickness TEM excision, distally placed lesions and a long interval (> 7 weeks) to CS were likely to have an inferior TME specimen. The results confirm that CS after TEM does not negatively influence local recurrence and survival, but the reduced disease‐free survival in patients with an inferior specimen is of concern.